Pengembangan Biji Kelor dan Biji Pepaya (Biokoagulan IKEYA) Pada Pengolahan Limbah Cair Domestik Menggunakan Analisis TOPSIS - Manulangga, Oktavina G. LP; Da Costa, Madalena (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2025)
Clean water in Kupang City has decreased in quantity by 30-50% with yellowish water quality and contains 45/100 ml of Collifom and E.coli bacteria that can cause diarrhea, salmonellosis, leptospirosis, hepatitis. One of the causes of the decrease in water quantity and quality is climate change, as well as extreme weather so that the available raw water sources are not sufficient to meet domestic needs, while 80% of clean water use comes from domestic sources. Therefore, it is necessary to utilize domestic wastewater through a coagulation-flocculation process using natural coagulants from Moringa seeds and papaya seeds which function as flocculants, reduce the characteristics of chemical contaminants, stabilize colloidal particles and absorb dissolved organic matter and are safe for human health and the environment. Research on the development of moringa seed and papaya seed biocoagulants needs to be done because they are very effective in reducing the concentration of pollutants and are economical. The research method is through laboratory analysis, TOPSIS analysis and proximate analysis to determine the levels of water, oil and fat, protein to produce pure coagulants. Then optimization of the coagulation-flocculation process with jar tests using TOPSIS analysis to determine the optimum conditions with a coagulant dose of 110 mg/L, a fast stirrer of 200 rpm for 1 minute, a slow stirrer of 60 rpm for 20 minutes, and a settling of 15 minutes with a percentage reduction using Moringa seeds and papaya seeds of 31.25% - 98.81% in TSS, Phosphate, Ammonia, Oil and Fat, Coliform.